Interpretation of the Sufism Teachings of Sunan Bonang in the Context of Javanese Culture - Ngatmin Abbas; Meti Fatimah; Alfian Eko Rochmawan; Mohammed Hafiz Ali Wafa (Yayasan Azhar Amanaa Yogyakarta, 2023)
This research aims to analyze the interpretation of Sunan Bonang's teachings of Sufism in the context of Javanese culture. The method used in this study is a literature study with content analysis. The results of this study indicate that Sunan Bonang's teachings of Sufism are uniquely interpreted in the context of Javanese culture, emphasizing the concept of unity between God and humans and integrating local wisdom into the teachings. In the Javanese culture context, Sunan Bonang's teachings of Sufism view that divinity is the essence of human life. Additionally, these teachings also integrate values of local wisdom such as mutual cooperation, simplicity, and humility in their practice of Sufism. Overall, Sunan Bonang's teachings of Sufism have strong relevance to the challenges of modern times, especially in developing spirituality and facing complex issues in the modern world